116 Problems in Algebra
Problems’ Proposer: Mohammad Jafari ^{∗} November 25, 2011
116 Problems in Algebra is a nice work of Mohammad Jafari. Tese problems have been published in a book, but it is in Persian (Farsi). Problems are very nice, so I ^{1} decided to collect a set of solutions for them. I should thank pco , socrates , applepi2000 , Potla, goldeneagle , and professordad who solved the problems and posted the solutions ^{2} .
Remark. A very few number of problems remained unsolved on AoPS. I will add the solutions of those problems as soon as I ﬁnd the book wr itten by Mr. Jafari. As this happened, problems’ numbers are not the same as the ﬁle posted on AoPS by the author ^{3} : they are consecutive.
^{∗} User momed66 in AoPS website
^{1} Amir Hossein Parvardi
^{2} Topic in AoPS: http://www.artofproblemsolving.com/Forum/viewtopic.php?t=444651
^{3} Topic in AoPS: http://www.artofproblemsolving.com/Forum/viewtopic.php?t=406530
1
1 FUNCTIONAL EQUATIONS
2
1 Functional Equations
1. Find all functions f (x) from R → R that satisfy:
f (x + y ) = f (x)f (y ) + xy
Solution. [First Solution] [by pco ^{4} ] Let P (x, y ) be the assertion f (x + y ) =
f (x)f (y ) +
then a such that f (a )
=
xy . Let f (1) = u . Tthe
0 : P (a, 0)
function f (x) = 0 ∀x is not a Solution. Let
f (a )(f (0) − 1) = 0 and so f (0) = 1.
f (− 1) = ^{2}
u
=⇒
u =
2
_{u} (u ^{2} + 1) − 2
=⇒
=⇒
f (1)f (− 1) = 2 =⇒
•
•
•
P (− 1 , 1)
P (1 , 1)
=⇒
=⇒
f (2) = u ^{2} + 1
P (− 1 , 2)
=⇒
f (1) = f (− 1)f (2) − 2
u ^{2} − 2 u + 2 = 0, impossible
And so no solution.
Solution. [Second Solution] [by applepi2000] Let P (x, y ) be the above assertion.
Then:
P (0 , y ) =⇒ f (y ) = f (0)f
(y ).
So, either f (y ) is always 0, which isn’t a solution (test x = y = 1), or f (0) = 1.
Thus f (0) = 1 and:
Let x = 2 a . Then:
P (x, − x) =⇒ f (x)f (− x) − x ^{2} =
1 .
1 + 4 a ^{2} = f (− 2 a )f (2 a ) =
(f (a ) ^{2} + a ^{2} )(f (− a ) ^{2} + a ^{2} ) ≥ a ^{4} .
However, taking large a , such as a = 42, this is false. So, no such function
exists.
^{4} Here: http://www.artofproblemsolving.com/Forum/viewtopic.php?t=378997
1 
FUNCTIONAL EQUATIONS 
3 
2. 
Find all functions f (x) from R \ { 1 } → R such that: f (xy ) = f (x)f (y ) + xy 
∀x, y ∈ R \ { 1 } .
Solution. [by pco] According to me, domain of functional equation must also
contain xy = 1.
Let then g (x) = ^{f} ^{(} ^{x} ^{)} deﬁned from (1 , + ∞) → R .
x
The equation becomes P (x, y ) : g (xy ) = g (x)g (y ) + 1.
Let
Let then m = inf _{x}_{>} _{1} g (x) and a _{n} a sequence of reals in (1 , + ∞) such that
x > 1 : P ( ^{√} x, ^{√} x ) =⇒ g (x) = g ( ^{√} x ) ^{2} + 1 ≥ 1.
lim _{n}_{→}_{+} _{∞} g (a _{n} ) = m .
• P ( ^{√} a _{n} , ^{√} a _{n} ) =⇒ g (a _{n} ) = g ( ^{√} a _{n} ) ^{2} + 1 ≥ m ^{2} + 1.
Setting n → + ∞ in this inequality, we get m ≥ m ^{2} + 1, impossible. So no
solution.
3. Find all functions f : Z → Z such that:
f (x) = 2 f (f (x)) ∀x ∈ Z.
Solution. [by Rust and mavropnevma ^{5} ] From f (x) = 2 f (f (x)) we get 2  f (x).
But then 2  f (f (x)), so 4
this, we have 2 ^{n}  f (x) for
8  f (x). Repeating
 f (x). But then 4 
f (f (x)), so
all n ∈ N , so f (x) ≡ 0.
4. Find all functions f : Z → Z and g : Z → Z such that:
f (x) = 3 f (g (x)) ∀x ∈ Z.
Solution. [by tkrass ^{6} ] f (g (x)) ∈ Z, so 3 f (x) for all x ∈
and 9 f (x) for all x. By easy induction we get that f (x) is divisible by any power
Hence 3 f (g (x))
Z.
of 3, hence f (x) ≡ 0. And g (x) may be any function taking integer values.
^{5} Here: http://www.artofproblemsolving.com/Forum/viewtopic.php?t=378363
^{6} Here: http://www.artofproblemsolving.com/Forum/viewtopic.php?t=378998
1 
FUNCTIONAL EQUATIONS 
4 
5. 
Find all functions f : Z → Z such that: 
7 f (x) = 3 f (f (x)) + 2 x ∀x ∈ Z.
Solution. [by Sansa ^{7} ] Let f (x) = g (x)+ 2 x, substituting in the main equation we get:
7(g (x) + 2 x) = 3 f (g (x) + 2 x) + 2 x =⇒
7 g (x) + 12 x = 3(g (g (x) + 2 x) + 2 g (x) + 4 x) =⇒
g (x) = 3 g (g (x) + 2 x)
Now let t (x) = g (x)+ 2 x, so we have: g (x) = 3 g (t (x)) At ﬁrst we found out that
3 g (x) =⇒ 3 g (t (x)) =⇒ 9 g (x) · · · . Thus 3 ^{n}  f (x) = 2 x ∀x ∈ R .
g (x) ∀n ∈ N , so g (x) ≡ 0 =⇒
6. Find all functions f : Q → Q that for all x, y ∈ Q satisfy:
f (x
+ y + f (x + y )) = 2 f (x) + 2 f (y ).
Solution. [by socrates] Put y := 0 to get
f (x + f (x)) = 2 f (x) + 2 f (0).
Now, put x := x + y into the last equality to get
f (x + y + f (x + y )) = 2 f (x + y ) + 2 f (0).
This, together with the initial, gives
f (x + y ) − f (0) = f (x) − f (0) + f (y ) − f (0),
so f (x) = ax + b. Substituting into the original equation, we ﬁnd the solutions:
^{7} Here: http://www.artofproblemsolving.com/Forum/viewtopic.php?t=378999
1 FUNCTIONAL EQUATIONS
•
•
f (x)
f (x) = − 2 x, ∀x.
= x,
∀x
7. Let f : R → R be a function that for all x, y ∈ R satisﬁes:
f (x + f (x) + y ) = x Prove that f is a bijective function.
+ f (x) + 2 f (y ).
5
Solution. [by socrates] Let P (x, y ) 
: f (x + f (x) + y ) = x + f (x) + 2 f (y ). 

Consider a, b 
such that f (a ) = f (b ). 
Then P (a, b ), P (b, a ) give a = b. So f is 
injective. 

Putting y 
:= − f (x) we get 
so f is clearly surjective.
f (− f (x)) = − ^{x}
2 ^{,}
Actually, no such function exists: Put y := 0 , x := − f (0) so, since f (− f (0)) =
0 , f (0) = 0 . So x := 0 gives f ≡ 0 which is not a solution .
8. Find all functions f : R → R such that for all real x, y we have:
f (x + f (x) + 2 y ) = x + f (f (x)) + 2 f (y ).
Solution. [by applepi2000] Let P (x, y ) be the above assertion, let a be an
arbitrary real number. Then:
P (− 2 a, a ) =⇒ f (a ) = a.
We’re done!
9. Given a function f : R → R such that:
f (x
+ f (x) + 2 y ) = x + f (x) + 2 f (y ).
Prove that f is bijective and that f (0) = 0.
1 FUNCTIONAL EQUATIONS
6
Solution. [by applepi2000] Let P (x, y ) be the above assertion.
P (x, − ^{f} ^{(}^{x}^{)} ) =⇒ − ^{x} =
2
2
f (− ^{f} ^{(}^{x}^{)} ).
2
So f is surjective. Now assume f (a ) = f (b ),
a = b and thus f is injective.
f
then from above − ^{a}
2
− ^{b} , so
2
=
Finally, let f (0) = n . Then from the above,
(− ^{n} ) = 0 =⇒ f (0) = ^{n} . So n = 0 and f (0) = 0 as desired.
2
4
10. Find all functions f : R ^{+} → R ^{+} such that for all x > y > 0 we have:
1
f (x − y ) = f (x) − f (x)f ( _{x} )y.
Solution. [by Dijkschneier ^{8} ]
1
• P (x, y ) : f (x − y ) = f (x) − f (x)f ( _{x} )y
• f (x − y ) > 0 =⇒ f (x)(1 − yf ( _{x} )) > 0
•
• y → x =⇒ _{x} ≥ f (
• =⇒ x ≥ f (x)∀x > 0
• 1 > y > 0 , P (1 , y ) =⇒ f (1 − y ) = f (1) − f (1) ^{2} y
Now take in particular 1 > y >
• 1 − y ≥ f (1) − f (1) ^{2} y
• 1 − f (1) ≥ y (1 − f (1))(1 + f (1))
• (1 − f (1))(1 − y (1 + f (1))) ≥ 0
•
•
So f (1 − y ) = 1 − y , and hence f (y ^{′} ) = y ^{′} ∀1 > y ^{′} > 0.
•
For 0 < x < 1, we have x = f (x) and so from the inequality
1
=⇒
_{y}
> f (
x ^{)}
1
1
1
1
x ^{)}
1
(1+ f (1)) ^{a}^{n}^{d} ^{s}^{o}^{:}
=⇒
=⇒
=⇒
=⇒
=⇒
f (1)
≥ 1
f (1) = 1
1
x − y ≥ f (x − y ) = f (x) − f (x)f ( _{x} )y
=⇒ x − f (x)
≥ y (1 − f (x)f (1 /x))
1
x ^{=}
1
f ( x ) ^{≤}
1
f ( _{x} ) ≤ _{x} , that is, f ( _{x} ) = x ^{1} ^{.}
1
1
^{8} Here: http://www.artofproblemsolving.com/Forum/viewtopic.php?t=424694
1 FUNCTIONAL EQUATIONS
Hence f (x) = x∀x > 1 and so in conclusion:
conversely is a solution.
7
f (x) = x∀x > 0, which
11. Find all functions f : R → R such that
for all x, y ∈ R .
f (f (x + f (y ))) = x + f (y ) + f (x +
y ),
+ f (y ))) = x + f (y ) +
f (x + y ) If f (a ) = f (b ) for some a, b , then, comparing P (x − b, a ) and P (x − b, b ), we get f (x) = f (x + a − b ) ∀x But then, comparing P (x, y ) and P (x + a − b, y ), we get x = x + a − b and so a = b and f (x) is injective.
Solution. [by pco] Let P (x, y ) be the assertion f (f (x
P (− f (x), x)
=⇒
f (f (0))) = f (x − f (x)) and so, since injective : f (0) =
x − f (x) and f (x) = x + a , which
is never a solution.
So no solution.
12. Find all functions f : R ^{+} ∪ { 0 } → R ^{+} ∪ { 0 } such that
for all x, y ∈ R ^{+} ∪ { 0 } .
f (f (x +
f (y ))) = 2 x + f (x + y ),
Solution.
If f (a ) = f (b ) for some a, b , then, comparing P (x, a ) and P (x, b ), we get
f (x + a ) = f (x + b ) ∀x But then, comparing P (x + a, y ) and P (x + b, y ), we get a = b and so f (x) is injective.
[by pco] Let P (x, y ) be the assertion f (f (x + f (y ))) = 2 x + f (x + y )
P (0 , x) =⇒ f (f (f (x))) = f (x) and,
So P (x, 0) becomes x + f (0) = 2 x +
since injective, f (f (x)) = x f (x) and so f (x) = f (0) − x which is
never a Solution 1. (since < 0 for x great enough)
1 
FUNCTIONAL EQUATIONS 
8 
So no solution. 

13. 
Find all functions f : R → R such that for all x, y ∈ R : 
f (x + f (x) +
2 f (y )) = x + f (x) + y + f (y ).
Solution. [by socrates] Putting x := 0 we see that f is injective. Put x :=
y, y := x to get
f (x + f (x) + 2 f (y )) = x +
f (x) + y + f (y ) =
f (y + f (y ) + 2 f (x)),
so x + f (x)+ 2 f (y ) = y + f (y )+ 2 f (x) =⇒ f (x) − x = f (y ) − y, that is f (x) − x
is constant: f (x) = x + c.
Substituing, we ﬁnd
f (x) = x, ∀x.
14. Find all functions f : R → R such that for all x, y ∈ R :
f (2 x + 2 f (y )) = x + f (x) + y + f (y ).
Solution. [by socrates] As in the previous problem,
f (2 y + 2 f (x)) so f (x) =
we get f (2 x + 2 f (y )) =
x + c. Substituing, we ﬁnd f (x) = x, ∀x.
15. Find all functions f : R → R such that for all x, y ∈ R satisfy:
f (f (x) + 2 f (y )) = f (x) + y + f (y ).
Solution. [by socrates] Putting x := 0 we see that f is injective. Put y := − f (x)
to ﬁnd f (− f (x)) = − f (x). So,
is
x := − f (y ) gives f (f (y )) = y and so f is
surjective. Finally, put y := 0 to get f (f (x) + 2 f (0)) = f (x) + f (0). Since f
surjective we get f (x) = x + c. Substituing, we ﬁnd f (x) = x, ∀x.
16. Find all functions f
all x, y ∈ R • f (x) + f (− x) = 0 for all x ∈ R ^{+} • The number of the elements of the set { x ∈ R f (x) = 0 } is ﬁnite.
+ f (y )) = f ^{2} (x) + f (y ) for
:
R → R such that • f (x ^{2}
1 FUNCTIONAL EQUATIONS
9
Solution. [by socrates] Assume f (x) > x for each x = 0 . Then 0 = f (x) +
f 
(− x) > x − x = 0 contradiction. So f (a ) ≤ a for some a = 0 . 

Put x := ^{} a − f (a ), y := a into the ﬁrst condtion to get f (a ) = f ^{2} ( ^{} a − f (a ))+ 

f 
(a ) =⇒ f ( ^{} a − f (a )) = 0 , so f (c ) = 0 for some c. Now put x, y := c and we get f (c ^{2} ) = 0 and by induction f (c ^{2} ^{n} ) = 0 . If 

c 
= 0 , 1 , − 1 then Observe that 
third condition is false. So c = 0 , 1 , − 1 . 

if f (k ) > k (f (k ) 
< k ) then f (− k ) < − k (f (− k ) > − k ) so for 
each x = 0 we have f (x) = x, x + 1 , x − 1 . If f (l ) = l − 1 for some l (the case f (l ) = l + 1 reduses to f (− l ) = − l − 1)
then f (1) = 0 . So
f (1 + f (y )) = f (y ).
• If 
f (2) 
= 
2 
then 
f (3) 
= 
2 and so f (9) = f ^{2} (3) = 4 , impossible. 
• If 
f (2) 
= 
1 
then 
f (4) 
= 
f ^{2} (2) = 1, impossible. 
• f (2) = If 
3 
then 
f (4) 
= 9 , impossible. 
Thus, f (x) = x, ∀x = 0 . Finally, x := 0 gives f (0) = 0 so the only solution
is f (x) = x.
17. Let f : R → R be an injective function that for all x, y ∈ R satisﬁes:
f (x + f (x)) = 2 x.
Prove that f (x) + x is a bijective function.
Solution. [by socrates] Let x + f (x) = g (x). So f (g (x)) = 2 x. g is clearly injective. Take y ∈ R , arbitrary and let f (y ) = 2 z = f (g (z )) so by injectivity of f we get g (z ) = y. We’re done.
18. Find all functions f : R → R such that :
f (x + f (x) +
2 f (y )) = 2 x + y + f (y ) ∀x, y ∈ R .
Solution. [by mousavi ^{9} ] It is obvious that f is injective.
^{9} Here: http://www.artofproblemsolving.com/Forum/viewtopic.php?t=378130
1 FUNCTIONAL EQUATIONS
10
• x 
= 
y = 0 =⇒ f (3 f (0)) = f (0) 
=⇒ 
f (0) = 0 

• y 
= 
0 =⇒ 
f (x + f (x)) = 2 x 

• x = 
0 =⇒ 
f (2 f (y )) = y + f (y ) 
=⇒ 
ff (2 f (y )) = 2 y 
Put f (2 f (y )) instead of y =⇒ 
f (x + f (x) + 4 y ) = 2 x + 
f (2 f (y )) + 2 y 
• x = 0 =⇒ f (4 y ) = 2 y + f (2 f (y )) 

• f (f (4 y ) − 2 y ) = 2 y + f (y + f 
(y )) 

• f (4 y ) − f (y ) = 3 y 

• y = − 2 x =⇒ f (x + f (x) + 2 f (− 2 x)) = f (− 2 x) 

• + 2 f (− 2 x) = 0 3 x + f (x) 

=⇒ − 6 x • + f (− 2 x) + 2 f (4 x) = 0 

• 2 f (x) = − f (− 2 x) 

• x = − 2 x, y = x =⇒ f (− 2 x + f (− 2 x) + 2 f (x)) = − 4 x 
+ x + f (x) 
• f (− 2 x) = 3 x + f (x)
− 2 f (x) = − 3 x + f (x)
• 
=⇒ f (x) = x. 

19. 
Let f, g, h : R → R be functions such that f is injective and h is bijective, 
satisfying f (g (x)) = h (x) for all x ∈ R . Prove that g is a bijective function.
Solution. [by socrates] Injectivity is obvious. Now take y ∈ R , arbitrary. There
exists z : 
h (z ) = f (y ) = f (g (z )) so by 
injectivity of f we get g (z ) = y. We are 
done. 
20. Find all functions f : R → R such that for all x, y ∈ R satisfy:
f (2 x +
2 f (y )) = x + f (x) + 2 y.
Solution. [by socrates] Putting x := 0 we see that f is bijective. We have
f (2 f (0)) 
= f (0) so f (0) = 0 . Put y := 0 to get f (2 x) = x + f (x). So the initial 
equation 
becomes f (2 x + 2 f (y )) = f (2 x) + f (2 f (y )) or f (x + y ) = f (x) + f (y ) 
from the surjectivity of f.
1 
FUNCTIONAL EQUATIONS 
11 

So, x + f (x) = f (2 x) = 2 f (x) =⇒ f (x) = x which is indeed a Solution 1. 

21. 
Find all functions f : R ^{+} ∪ { 0 } → R ^{+} such that for all x, y 
∈ 
R ^{+} ∪ { 0 } : 
_{f} _{(} x + f (x)
2
Solution. [by socrates] Put
+
y ) = f (x) + y.
_{y} _{:}_{=} ^{y}
+ f (y )
2
to get
So
_{f} _{(} x + f (x) _{+} y + f (y )
2
2
)
= f (x) + ^{y} ^{+} ^{f} ^{(}^{y} ^{)}
2
^{.}
_{f} _{(}_{y} _{)} _{+} x + f (x) _{=} _{f} _{(} x + f (x) _{+} y + f (y )
2
2
2
) = f (x) +
^{y}
^{+} ^{f} ^{(}^{y} ^{)}
2
so f (x) − x = f (y ) − y, that is f (x) − x is constant: f (x) = x + c. Substituing,
we ﬁnd f (x) = x, ∀x.
22. Find all functions f : R ^{+} ∪ { 0 } →
R ^{+} ∪ { 0 } such that for
_{f} _{(} x + f (x)
2
+ f (y )) = f (x) + y.
all x, y ∈ R ^{+} ∪ { 0 } :
Solution. [by socrates] Put x = y := 0 =⇒ f ( ^{3}^{f} ^{(}^{0}^{)} ) = f (0). Put x := 0 , y :=
2
3f (0)
2
_{:}
_{f} _{(} 3f (0) _{)} _{=} 5f (0)
2
2
so f (0) = 0 .
respectively.
The former implies that f is injective and the latter f (x) = x, which is indeed
a Solution 1.
Now, x := 0 and y := 0 give f (f (y )) = y and f ( ^{x} ^{+} ^{f} ^{(} ^{x} ^{)} ) = f (x),
2
be a function such that • f (x + y ) = f (x) + f (y ) for
all x, y ∈ R ^{+} ∪ { 0 } • The number of the elements of the set { xf (x) = 0 , x ∈ R ^{+} ∪ { 0 }} is ﬁnite. Prove that f is injective function.
23. Let f : R ^{+} ∪ { 0 } → R
1 FUNCTIONAL EQUATIONS
12
Solution. [by socrates] We easily ﬁnd f (0) = 0 . Suppose there exist a, b ≥ 0
such that a = b and f (a ) = f (b ). Wlog assume a > b. Then f (a ) = f (a − b + b ) =
f (a − b ) + f (b ) so f (c ) = 0 for some c = 0 . So, by induction, f (2 ^{n} c ) = 0 for each
n ∈ N , contradicting the second condtion. So f is injective.
24. Find all functions f : R ^{+} ∪ { 0 } → R such that i) f (x + f (x) + 2 y ) =
f (2 x) + 2 f (y ), for all x, y ∈ R ^{+} ∪ { 0 } ii) The number of the elements of the set { xf (x) = 0 , x ∈ R ^{+} ∪ { 0 }} is ﬁnite.
Solution. [by goldeneagle ^{1}^{0} Let P (a, b ) be the assertion. Let A be the set
which mentioned in the second condition. Deﬁne ^{k} = M ax(A).
2
If x > f (x) then P (x, ^{x} ^{−} ^{f} ^{(} ^{x} ^{)}
2
_{)}
_{⇒} _{f} _{(} x − f ( x )
2
) = 0 ⇒ f (x) ≥ x − k so ∀x ∈
R ^{+} ∪ { 0 } : f (x) ≥ x − k
I want to prove that
t = b − a .
(I).
f is injective. If not, then ∃a < b :
f (a ) = f (b ). Deﬁne
•
•
P
P ( ^{a} , ^{x} ), P ( , ^{x} ), (I) ⇒ ^{a} + f ( ^{a} ) = ^{b} + f ( ) (II)
2
2
b
2
2
2
2
2
b
2
b
P (a, ), P (b, ^{a} ), (II)
2
2
⇒ f (2 a ) − f (2 b ) = t (III)
(a, x), P (b, x), (III) ⇒ ∀x ≥ a + f (a ): f (x) − f (x + t ) = t . But f (x) ≥ x − k ,
so this is contradiction! (t > 0)
Now I want to prove that f (0) = 0. Deﬁne c = f (0). If c < 0, then
(0 , − ^{c} ) ⇒ f (− ) = 0 and since f is injective we should have c = 0, contra
P
diction!
2
c
2
So c ≥ 0. We have
• P (0 , 0) ⇒ f (c ) = 3 c
• P (0 , x) 
⇒ f (2 x + 
c ) = 2 f (x) + c (*) 
• P (c, x) 
⇒ f (2 x + 
4 c ) = 2 f (x) + f (2 c ) (**) 
• (*), (**) ⇒ f (2 x + 4 c ) − f (2 x + c ) = f (2 c ) − c ⇒ (x = ^{c} )f (5 c ) =
2
Put x = 2 c in (*): f (5 c ) = 2 f (2 c )+ c , so c = 0 and then P (x, 0) ⇒
2 f (2 c ) − c
f (x) = x.
^{1}^{0} http://www.artofproblemsolving.com/Forum/viewtopic.php?t=442600
1 
FUNCTIONAL EQUATIONS 
13 
25. 
Find all functions f : R → R such that: • f (f (x) + 
y ) = x + f (y ) for all 
x, y ∈ R • for each x ∈ R ^{+} there exists some
y ∈ R ^{+} such that f (y ) = x.
Solution. [by socrates] Put y := 0 to
bijective. So, since f (f (0)) = f (0) we
get f (f (x)) = x + f (0) that is f is
0 . So f (f (x)) = x and
have f (0) =
f 
(x + y ) = f (x) + f (y ). Since f bijective, for each x 
> 0 there exists unique 
y 
= f (x) such that f (y ) = x, so second condition means f (x) > 0 for each 

x 
> 0 . 
It is well known that since f is Cauchy function, it is increasing so f (x) = cx
and substituing f (x) = x.
26. Find all functions f : R → R such that • f (f (x) + y ) = x + f (y ) for all
x, y ∈ R • The set { x ∈ R f (x) = − x} has a ﬁnite number of elements.
Solution. [by socrates] Put y :=
Hence, f (0) =
0 to get f (f (x)) = x
+ f (0) so f is bijective.
0 , f (f (x)) = x and f (x + y ) = f (x) + f (y ).
Let g (x) = f (x) + x. Then g (x + y ) = g (x) + g (y ). If g (a ) = 0 for some a = 0
So g (x) = 0 ⇐⇒ x = 0 .( ^{∗} )
Then f (a ) = f (a − b + b ) = f (a − b ) +
Now, take a, b such that f (a )
then g (2 ^{n} a ) = 0 , ∀n ∈ N , contradiction.
= f (b ).
f
( ^{∗} )
(b ) =⇒ f (a − b ) = 0 =⇒ a = b. Thus, g is injective.
We have g (f (x)) = f (f (x)) + f (x) = x + f (x) = g (x) =⇒ f (x) =
x.
27. Find all functions f : R → R such that for all x, y, z ∈ R :
f (f (f (x)) + f (
Molto più che documenti.
Scopri tutto ciò che Scribd ha da offrire, inclusi libri e audiolibri dei maggiori editori.
Annulla in qualsiasi momento.